Uporaba referenčnih arhitektur pri gradnji informacijsko integriranega podjetja - Vujica-Herzog, Nataša (Strojniški vestnik, 2000)
The rather uncontrolled and unharmonised building of information systems that has taken place over the years means that today many workshops are equipped with software and hardware with different times of production, unequal levels of connectivity and updating of functions. This of course, is crucial for the performance of an information system 1. This paper presents a holistic approach to the development of an information-integrated enterprise. It is based on reference architectures and is meant to fill the gap occuring in this field.
Keywords: sistemi informacijski; arhitektura referenčna; integracije podjetij; informacijski sistemi; arhitektura (računalnik); integracija; podjetja